Invasive Marine species evaluated within the Gulf of Guayaquil. Case Study. Shrimp Field , 2011 - Torres Ch, Gladys (Revista Universidad de Guayaquil, 2013)
The problems of exotic or invasive species is involved in different anthropogenic activities, known as pests or plague species in terrestrial and aquatic environments, also altering biodiversity and human health, establishing the necessity to implement preventive strategies locally and regionally. Prospective Investigation Methodology was used with the objective of registering the aquatic invasive species thorough records and surveys in some shimp farms located on the coastal border of the Estero Salado and the Rio Guayas (Inner Gulf of Guayaquil) they are navigable canals, the mayor areas of aquative production and mangrove. The results showed invasive species which have local and worldwide records. The negative perception of these species is the problem that causes in the growth of shrimp, and the economic losses due to the cost of supplies, materials and pond cleaning, however the infestation of mollusks which function is to act as “ biological filters ” would be considered as bioremediation of the water quality, which is positive for the ecosystem of the Gulf for the removal of carbon , and as biological indicators they establish the necessity of broadening the study nationally and implementing strategies for the integral management.
Keywords: Invasive Marine Species; Ballast Water; Plankton; Nonnative invertebrate; Gulf of Guayaquil; Mangrove; Shrimp Aquaculture